HISTOPATHOLOGICAL DESCRIPTION OF BROILER CHICKENS INFUSED WITH DADAP LEAVES AND EXPERIENCED TRANSPORT STRESS - Habibi, Ryan Helmi; Winaya, Ida Bagus Oka; Merdana, I Made (Buletin Veteriner Udayana; Vol. 15 No. 5 October 2023DO - 10.24843/bulvet.2023.v15.i05.p02, 2023)
To get to the hands of consumers, it is necessary to transport broiler chickens from the warehouse to the marketing place. The transportation process often causes stress to broiler chickens, this is due to the long distance traveled when transportation is inadequate. This situation causes changes in organs, one of which is the lungs. Due to the potential of Dadap leaf as an antistress, this study aims to determine the effect of Dadap leaf infusion (Erythrina subumbrans) on pulmonary histopathology (Pulmonary ventilation) of broiler chickens experiencing transportation stress. A total of 30 male broiler chickens aged 4 weeks were taken as samples in this study. This study used a completely randomized design (CRD) with a factorial 3×2×5 pattern with three replications and the number of samples used were 30 broiler chickens which were divided into 5 treatment groups, namely negative control (P 0 ), vitamin C 2 grams/L (P 1 ), 1000 ppm Dadap leaf infusion (P 2 ), 2000 ppm Dadap leaf infusion (P 3 ) and 3000 ppm Dadap leaf infusion (P 4 ). The data obtained were analyzed using the Kruskal-Wallis test. If there is a difference, it is continued with the Mann-Whitney test. performed using a scoring method on five visual fields, with a score of one meaning mild/focal, two to three meaning moderate/multifocal, more than three meaning severe/diffusion. The results showed that the mean of pulmonary histopathological damage with accurate variables was significantly different. The data obtained were the highest damage occurred in the P 0 group (negative control) and the lowest damage occurred in the P 3 group (3000 ppm dadap leaf infusion). The conclusion of this study is that 10% Dadap leaf infusion can reduce pulmonary damage and can be used as an antioxidant.